High dielectric permittivity and low loss of polyvinylidene fluoride filled with carbon additives: Expanded graphite versus reduced graphene oxide. (September 2019) - Deng, Wei; Yu, Weili; Cui, Weiwei; Guo, Huachao; Liu, Yifan; Zhao, Tianqi
Polymer dielectric composites with high dielectric permittivity and low dielectric loss play an increasing important role for modern electronic and electric industry. In this study, polyvinylidene fluoride (PVDF) incorporated with expanded graphite (EG) or reduced graphene oxide (rGO) was prepared by solution casting and the following hot pressing. The structure, morphology, and properties of the obtained products were characterized. In comparison with EG, rGO exhibits well dispersion and strong interaction with PVDF matrix. With the increasing content of conductive fillers, the dielectric permittivity of both PVDF/EG and PVDF/rGO composites shows an increasing trend whereas the dielectric loss keeps at a low level. The dielectric permittivity of PVDF filled with 4 wt% EG and 8 wt% rGO reaches 420 and 38 at 100 Hz, respectively. Moreover, the introduction of EG and rGO improves the mechanical strength and the thermal stability of PVDF matrix.